Development of GPCR Modulation of GABAergic Transmission in Chicken Nucleus Laminaris Neurons - Tang, Zheng-Quan (Public Library of Science, 2012)
Neurons in the nucleus laminaris (NL) of birds act as coincidence detectors and encode interaural time difference to localize the sound source in the azimuth plane. GABAergic transmission in a number of CNS nuclei including the NL is subject to a dual modulation by presynaptic GABA(B) receptors (GABA(B)Rs) and metabotropic glutamate receptors (mGluRs). Here, using in vitro whole-cell patch clamp recordings from acute brain slices of the chick, we characterized the following important but unknown properties pertaining to such a dual modulation: (1) emergence of functional GABA synapses in NL neurons; (2) the temporal onset of neuromodulation mediated by GABA(B)Rs and mGluRs; and (3) the physiological conditions under which GABA(B)Rs and mGluRs are activated by endogenous transmitters. We found that (1) GABA(A)R-mediated synaptic responses were observed in about half of the neurons at embryonic day 11 (E11); (2) GABA(B)R-mediated modulation of the GABAergic transmission was detectable at E11, whereas the modulation by mGluRs did not emerge until E15; and (3) endogenous activity of GABA(B)Rs was induced by both low- (5 or 10 Hz) and high-frequency (200 Hz) stimulation of the GABAergic pathway, whereas endogenous activity of mGluRs was induced by high- (200 Hz) but not low-frequency (5 or 10 Hz) stimulation of the glutamatergic pathway. Furthermore, the endogenous activity of mGluRs was mediated by group II but not group III members. Therefore, autoreceptor-mediated modulation of GABAergic transmission emerges at the same time when the GABA synapses become functional. Heteroreceptor-mediated modulation appears at a later time and is receptor type dependent in vitro.